Smart specialisation in innovative environment - Miszczak, Katarzyna (Inteligentna specjalizacja w innowacyjnym środowisku, 2018)
The study offers a new reading of innovative environment, which when taken together constitute the basis for thinking about regions, society and space through the lens of smart specialisation. The aim of article is the identification and characterisation of the main features and challenges of smart specialisation, understood as a strategic approach to economic development through targeted support to research and innovation. This approach combines industrial, educational and innovation policies to suggest that countries or regions pinpoint and select a limited number of priority areas for knowledge- -based investments, focusing on their strengths and comparative advantages. In the article, three case studies (from Poland, the Czech Republic and Turkey) of different types of implementation of smart specialisation illustrate the utility of the intelligent policies
Biblioteka Regionalisty, 2018, Nr 18, s. 39-49
Keywords: smart specialisation; knowledge; R&D; innovative environment; regional growth; inteligentna specjalizacja; wiedza; B+R; innowacyjne środowisko; rozwój regionalny